Towards realistic simulation of DNA-based molecular communication networks - Kaussow, Max; Peters, Robert; Scheer, Sarah; Hyttrek, Christian; Fischer, Stefan; Lau, Florian (Frontiers in Communications and Networks, 2026)
Next to further miniaturization, the process of self-assembly has great potential for construction, computation, and even communication at the nanoscale. DNA-based self-assembly is an especially promising candidate as it is possible to create entire nanonetworks from just DNA from already existing and comparably cheap building blocks. As wet-lab experiments are still fairly expensive and complex, and self-assembly is hard to predict, simulation tools are crucial for the rapid prototyping of new ideas. However, current self-assembly simulators mainly focus on computational and construction aspects. In this paper, we present a new model for our NetTAS simulator, kTHAM, which simulates the possible interactions of very large numbers of DNA structures simultaneously and measures the process in real-time. This allows for a much more realistic analysis of DNA-based nanonetworks as compared to what is possible with other simulators and with the other models of NetTAS.